Perbuatan Melawan Hukum Dan Menyalahgunakan Wewenang Dalam Tindak Pidana Korupsi - Indra Gunawan (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2020)
Acts against the law and abuse of authority in a criminal act of corruption are elements that determine whether or not an act can be declared a criminal act. Both of these acts are important to distinguish the boundaries in criminal acts of corruption and also interesting to talk about.There are two legal subjects in a criminal act of corruption, namely a person or every person and corporation as perpetrators and those who can be held liable for criminal acts of corruption committed by their management. Against the law (wederrechtelijk) is one of the elements of a criminal offense in article 2 paragraph (1)of the UUPTPK namely the special unlawful nature. It is referred to as a special unlawful nature because the word against law is explicitly stated in the offense formulation in article 2 paragraph (1) of the UUPTPK. Abusing is defined as the existence of rights or powers that are not carried out properly as it has benefited others, children, grandchildren, family or cronies.There is also misusing the opportunity or time on the perpetrators in connection with the position. Misusing advice means abusing equipment or facilities attached to the perpetrator because of his position.Key-words : Against the Law, Abuse, authority, Corruption Crime